半橋串聯共振式磁奈米粒熱療加熱系統研製 - 陳建璋; Chen, Chien-Chang (2007)
所謂磁奈米熱療乃是利用直徑7到50奈米( nm)的氧化鐵(Fe3O4)顆粒，於外加交流磁場下將奈米磁粒加溫至42℃以上，以達到殺死癌細胞的目的。在系統的設計上必須設計一套效率高、磁場輻射集中且可變頻的電磁加熱系統。本研究採用半橋串聯交換式電路來構成系統主體，並利用在驅動電路上變頻的設計來對奈米磁粒進行溫昇實驗。為了讓系統有更好的溫昇效果，於是著重在高頻電磁輻射線圈結構較佳化設計，藉以提高系統磁場輻射的效率，並且探討線圈阻抗對於熱的相關影響特性。因為在電路系統振盪槽內整體阻抗值必須維持不變，才可以讓電流值維持在定值，相對的線圈所輻射出的磁場也可以維持在定值；於是使用阻抗分析儀量測線圈阻抗，探討在加熱的過程中，熱對於線圈阻抗值參數影響的程度，以做為線圈繞製上改進的依據，以提高系統整體的穩定度。在線圈結構上的設計上，採用有限元素法模擬軟體來改善線圈結構，藉以找出對於奈米磁粒而言比較均勻和集中的磁場輻射匯集處，並以實際繞製的線圈組進行加熱實驗。實際的加熱實驗結果顯示，使用特別設計的線圈及加熱系統，已經成?的將奈米磁粒溶液在半小時左右加熱達到6℃的溫昇，達到本研究所需要的溫昇效果。 The main idea of magnetic nanoparticle thermotherapy is to utilize 7- to 50-nm diameter of ferric oxide (Fe3O4) particles which are heated up to 42℃ under AC magnetic field for cancer theorpy applications In order to achieve the goal of killing cancer cells using the AC magnetic field we designed a heating system to generate magnetic field which can be focused and frequency adjustable This study adopts the half-bridge series-resonant type circuit as the core scheme of the heating system and utilizes the frequency-adjustable design to conduct the heating experiment In this work we also study the characteristics of coil from impedance aspect to improve the heating efficiency of magnetic field Since the impedance value must be kept unchanged in the operation so as to make the current in coil and the magnetic field in a stable state the impedance analyzer is used in the light of raising the system stability and coil impedance measurement As for the design of coil structure we utilize finite-element simulation software (COMSOLTM) to find the place with evener and more concentrated magnetic field The experiment results show that the designed coil and the heating system can warm up the magnetic nanoparticle 6℃ in 30 minutes which has attained the expected heating result for the study